Kajian Ilmiah Kelakai (Stenochlaena palustris) sebagai Tanaman Sumber Fitoestrogen untuk Optimalisasi Laktasi - Atikah Nurul Fadhilah; Ardi Mustakim (CV. Muara Edukasi, 2026)
Kelakai (Stenochlaena palustris) is a fern plant traditionally used as food and medicinal plant. Recently, kelakai has gained scientific attention due to its bioactive compounds with potential phytoestrogenic activity, which mimic estrogen-like effects in the body. Phytoestrogens are known to play a role in lactation, particularly in supporting breast milk production. This study aims to review the scientific evidence regarding kelakai as a phytoestrogen source and its potential role in lactation optimization based on available literature. The method employed was a literature review of relevant national and international scientific articles related to kelakai, phytoestrogens, and lactation. The results indicate that kelakai contains secondary metabolites such as flavonoids and phenolic compounds that may contribute to phytoestrogenic activity. These compounds are reported to support hormonal balance and potentially enhance breast milk production. In conclusion, kelakai shows promise as a natural phytoestrogen source that may be developed to support lactation optimization and functional food applications.